Faktor yang Memengaruhi Perilaku Seks Pranikah pada Remajaa: Systematic Review - Rinda Intan Sari (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Adolescence is a period of searching for identity and any information, including pornography. Data states that premarital sexual behavior starts from adolescence in middle and high school. This happens, among other things, due to peers and parenting patterns. Parenting patterns and lack of discipline are associated with increased risky sexual behavior. analyzing parental parenting patterns and premarital sexual behavior in adolescents. The research design used was a Systematic Review. Journal search via Google Scholar, Researchgate, ScienceDirect databases. The inclusion criteria were determined, namely a maximum publication time span of 5 years (2017-2023), non-experimental correlation descriptive study with cross sectional, the languages used are Indonesian and English, original type of research article, full text. The results of a review of 10 articles that have been reviewed state that parenting patterns, peers & acceptance of information influence premarital sexual behavior of teenagers. Based on the results of a review of 10 journals, it is stated that teenagers with democratic parenting patterns have good sexual behavior or are not at risk and there are 7 journals stating that there are There is a significant relationship between parental parenting patterns and premarital sexual behavior among teenagers and there are 3 journals which state that premarital sexual behavior among teenagers is influenced by peers and receipt of information.